ANALISIS PENGARUH PRODUK DOMESTIK REGIONAL BRUTO, INFLASI, DAN SUKU BUNGA KREDIT TERHADAP PENANAMAN MODAL DALAM NEGERI DI RIAU TAHUN 2001 – 2015 - Ronal Iswandi; Rosyetti '; Rahmita Budiarti Ningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine how much influence the regional gross domestic product, inflation, and interest rates of loans to the Domestic Investment (DCI) in Riau Province in 2001-2015. This study is an analysis of secondary data to analyze factors affecting domestic investment in Riau Province in 2001-2015. The data used in this research is data that is time series from the years 2001-2015. Methods of analysis used is multiple linear regression analysis method. Tests conducted on the hypothesis and the reliability of the data (assuming a classic) premises /; on using a significant level of 5%, with the aid of SPSS data processing. The data used was taken from the Central Statistics Agency of Riau Province, Investment and Promotion Agency of Riau and Bank Indonesia in Riau Province. From the results of tests performed on this research note simultaneously that the independent variable is regional gross domestic product, inflation and lending rates by F test significant influence on Domestic Investment in Riau province is equal to 0.000. Individually, the variable regional gross domestic product amounted to 0,018 and the positive impact significantly on Domestic Investment in Riau province is equal to 0.000. Variable inflation negative effect of -4.211 and is not significant at 0.977 and lending rates by -722.082 and negative effect not significant at 0.851 to variable Domestic Investment (DCI) in the province of Riau.Keyword : Domestic Investment (DCI), Gross Domestic Product, Inflation and Interest Rates On Loans.